Study on the Performance of Different Modification Conditions on the Activity of Red Mud - Zhao, Aonan; Chen, Shiying (International Journal of Materials Science and Technology Studies, 2025)
Red mud is an industrial solid waste produced during alumina extraction from bauxite. This study aims to enhance red mud's reactivity and develop a composite cementitious material to increase its utilization rate. The methods used include individual red mud calcination and co-calcination with calcium carbide slag (RM-CS). The physical and chemical properties of red mud were assessed using X-ray diffraction (XRD) and thermogravimetric-differential scanning calorimetry (TG-DSC) analyses. Results show that dolomite (CaMg (CO3)2) in red mud starts to decompose at 500°C and is nearly fully decomposed by 900°C. The physical and chemical properties of the composite cementitious material were analyzed via XRD and compressive strength tests. The findings indicate that the 28-day compressive strength of the red mud composite material reaches 60 MPa, while the RM-CS composite material reaches 64 MPa. Toxicity leaching results indicate that the heavy metal ion content in the composite material complies with standard requirements, suggesting that the composite cementitious material is environmentally friendly.